2017
DOI: 10.1111/ger.12317
|View full text |Cite
|
Sign up to set email alerts
|

Tooth loss and its relationship with protein intake by elderly Brazilians—A structural equation modelling approach

Abstract: Objective: This study aimed at assessing the relationship between self-perceived tooth loss and wearing dentures, on the one hand, and the consumption of protein, on the other hand, among the elderly population of Botucatu, SP. Food consumption tends to decrease with ageing, especially protein intake, and one of the causes could be the precariousness of oral health. Several risk factors associated with deficient dietary protein intake have been identified, namely greater physical dependence, reduced caloric in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
22
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
0
22
0
1
Order By: Relevance
“…Periodontitis has been associated with poor glycemic control, higher risk of atherosclerosis and aspiration pneumonia . Tooth loss has been associated with poor dietary habits, as chewing efficiency is reduced and choice of food can be restricted . Tooth loss can also impact facial appearance and therefore affect self‐esteem and socialization .…”
Section: Introductionmentioning
confidence: 99%
“…Periodontitis has been associated with poor glycemic control, higher risk of atherosclerosis and aspiration pneumonia . Tooth loss has been associated with poor dietary habits, as chewing efficiency is reduced and choice of food can be restricted . Tooth loss can also impact facial appearance and therefore affect self‐esteem and socialization .…”
Section: Introductionmentioning
confidence: 99%
“…Models with complex interaction pathways and latent variables differ from ordinary regressions, which allow investigating just one outcome . In addition, they are useful for studying direct and indirect mechanisms whereby some associations are established.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of masticatory function and nutritional status on the general health and quality of life of the elderly has been extensively addressed in the literature [6,13,14]. A recent study has shown that patients with tooth loss above 20 teeth have lower consumption of healthy food and lower nutrient intake, which increases the risk of cardiovascular disease [13].…”
Section: Discussionmentioning
confidence: 99%
“…The presence of health teeth and functional dentures, as they are related to adequate nutrient consumption, may favor a good general health and quality of life of the elderly [5,6]. However, it is suggested that the absence of functional occluding tooth pairs worsens the chewing ability, which may lead to modifications in eating habits, food and nutritional intake, causing malnutrition [7,8].…”
mentioning
confidence: 99%